MetaReality: enhancing tactile experiences using actuated 3D-printed metamaterials in Virtual Reality - Feick, Martin; Degraen, Donald; Hupperich, Fabian; Krüger, Antonio (Frontiers in Virtual Reality, 2023)
During interaction with objects in Virtual Reality (VR), haptic feedback plays a crucial role for creating convincing immersive experiences. Recent work building upon passive haptic feedback has looked towards fabrication processes for designing and creating proxy objects able to communicate objects' properties and characteristics. However, such approaches remain limited in terms of scalability as for each material a corresponding object needs to be fabricated. To create more flexible 3D-printed proxies, we explore the potential of metamaterials. To this aim, we designed metamaterial structures able to alter their tactile surface properties, e.g., their hardness and roughness, upon lateral compression. In this work, we designed five different metamaterial patterns based on features that are known to affect tactile properties. We evaluated whether our samples were able to successfully convey different levels of roughness and hardness sensations at varying levels of compression. While we found that roughness was significantly affected by compression state, hardness did not seem to follow the same pattern. In a second study, we focused on two metamaterial patterns showing promise for roughness perception and investigated their visuo-haptic perception in Virtual Reality. Here, eight different compression states of our two selected metamaterials were overlaid with six visual material textures. Our results suggest that, especially at low compression states, our metamaterials were the most promising ones to match the textures displayed to the participants. Additionally, when asked which material participants perceived, adjectives, such as "broken" and "damaged" were used. This indicates that metamaterial surface textures could be able to simulate different object states. Our results underline that metamaterial design is able to extend the gamut of tactile experiences of 3D-printed surfaces structures, as a single sample is able to reconfigure its haptic sensation through compression.